2019
DOI: 10.1177/1559325819833840
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Delayed Homologous Recombination by Induction of Radioadaptive Response in RaDR-GFP Mice (Yonezawa Effect): An Old Player With a New Role

Abstract: Radiotherapy (RT) treats cancer effectively with high doses of ionizing radiation (IR) to killing cancer cells and shrinking tumors while bearing the risk of developing different side effects, including secondary cancer, which is most concerning for long-term health consequences. Genomic instability (GI) is a characteristic of most cancer cells, and IR-induced GI can manifest as delayed homologous recombination (HR). Radioadaptive response (RAR) is capable of reducing genotoxicity, cell transformation, mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In a series of our previous investigations, we demonstrated that induction of RAR could relieve IR-induced GI measured as micronucleus formation and delayed homologous recombination in the hematopoietic system. 15 , 16 Recently, we also verified the modifying effects from dietary factors on the biological response to IR exposure of mice. Our studies confirmed that there existed an interaction between life-style factors (i.e., high fat diet, low fat diet and alcohol drinking) and IR, which could lead to altered responses to IR in mice.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In a series of our previous investigations, we demonstrated that induction of RAR could relieve IR-induced GI measured as micronucleus formation and delayed homologous recombination in the hematopoietic system. 15 , 16 Recently, we also verified the modifying effects from dietary factors on the biological response to IR exposure of mice. Our studies confirmed that there existed an interaction between life-style factors (i.e., high fat diet, low fat diet and alcohol drinking) and IR, which could lead to altered responses to IR in mice.…”
Section: Discussionmentioning
confidence: 76%
“…6 - 12 In a series of previous studies using the RAR mouse model (Yonezawa Effect) which could rescue bone marrow death through induced resistance in the hematopoietic system, 13 , 14 we confirmed that RAR could reduce radiation-induced genotoxcity and GI measured as decreased frequency of micronucleus erythrocytes in bone marrow cells and reduced frequency of delayed homologous recombinant cells in bone marrow nucleated cells and splenocytes. 15 , 16 On the other hand, dietary and lifestyle-related factors could influence health in many species and play key roles in modulating the risk of developing cancer. As a fact, certain cancers are primarily dependent on dietary habits.…”
Section: Introductionmentioning
confidence: 99%
“…While RaDR and the analogous FYDR mice (which harbor a similar reporter for which recombinant cells are fluorescent yellow) have been used in many informative studies of mutagenesis in non‐malignant tissue (Kiraly et al ., 2014; Sukup‐Jackson et al ., 2014; Kiraly et al ., 2015; Kimoto et al ., 2017; Liu et al ., 2019), they had not yet been employed in the context of cancer. Since the structures and clonal dynamics of tumor tissue are quite unlike normal tissue architecture, we aimed to develop new approaches to evaluate RaDR mutations in tumors.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, when model mice were irradiated with 0.5 Gy Fe-ion beam, the HR frequency in bone marrow or spleen cells was observed to increase significantly. Additionally, we found that the HR frequency significantly decreased under a radioadaptive response-(RAR-) inducible condition when compared with that under a non-RAR-inducible condition [126]. 4.5.…”
Section: Genome Instabilitymentioning
confidence: 85%